Evaluasi Batuan Induk Formasi Talang Akar Bawah sebagai Prospek Hidrokarbon dan Warisan Geologi di Taman Nasional Bukit Duabelas, Sub-Cekungan Jambi - Muhammad Rus Dody Alfayed Rus; Anggi Deliana Siregar; Bagus Adithya; Ratu Anjani; M. Syaifudin (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The Bukit Duabelas National Park (BDNP) area, Sarolangun Regency, is located within the Jambi Sub-Basin, which forms part of the South Sumatra Basin and has long been recognized as a hydrocarbon-producing region. This study aims to evaluate the geochemical characteristics of the Lower Talang Akar Formation source rock, including organic matter quantity, quality, thermal maturity, organic matter origin, and depositional environment. The applied methods include Total Organic Carbon (TOC) analysis, Rock-Eval Pyrolysis, vitrinite reflectance (Ro), and biomarker analysis using Gas Chromatography (GC) and Gas Chromatography–Mass Spectrometry (GC–MS) on shale outcrop samples. The results indicate that the Lower Talang Akar Formation contains very good to excellent organic matter richness, with TOC values ranging from 3.18% to 4.71%. The organic matter quality is dominated by Type II kerogen, indicating a strong potential for oil generation. Biomarker analyses suggest that the organic matter is primarily derived from algal and bacterial sources with contributions from terrestrial input, deposited in a transitional (paralic) environment under anoxic to suboxic conditions. Based on Tmax values, vitrinite reflectance, and biomarker maturity parameters, the Lower Talang Akar Formation source rock is classified as thermally immature. Despite its immature maturity level, the geochemical characteristics indicate favorable hydrocarbon potential. These findings provide an important basis for further hydrocarbon exploration and support the designation of the Bukit Duabelas National Park area as a geological heritage (geoheritage) site with significant scientific value within the Jambi Sub-Basin.